Agents and Data Mining Interaction 10th International Workshop, ADMI 2014, Paris, France, May 5-9, 2014, Revised Selected Papers - Cao, Longbing; Zeng, Yifeng; An, Bo; Symeonidis, Andreas L.; Gorodetsky, Vladimir; Coenen, Frans; Yu, Philip S. (Lecture Notes in Artificial Intelligence, 2015)
This book constitutes the thoroughly refereed and revised selected papers from the 10th International Workshop on Agents and Data Mining Interactions, ADMI 2014, held in Paris, France, in May 2014 as satellite workshop of AAMAS 2014, the 13th International Conference on Autonomous Agents and Multiagent Systems. The 11 papers presented were carefully reviewed and selected from numerous submissions for inclusion in this volume. They present current research and engineering results, as well as potential challenges and prospects encountered in the respective communities and the coupling between agents and data mining.